Identifying The Factors Associated with Time to Discontinuation of Intrauterine Device Among Women of Reproductive Age at Arba Minch Town and Zuria Woreda, Gamo Zone, Southern Ethiopia - Gergiso, Kabtamu Tolosie; Kasika, Teshale Petros; Erango, Markos Abiso; Anjullo, Belay Belete (Ethiopian Journal of Reproductive Health, 2022)
Background: Intrauterine device (IUD) is the world’s most widely used reversible birth control method. This study was aimed to assess factors that influence the time to discontinuation of Intrauterine device among women who ever used IUD in Arba Minch Town and Zuria Woreda, Southern part of Ethiopia. Methods: A retrospective cohort study design was carried and stratified random sampling technique was used to determine sample of size 230 from a total population of 25,658 Women. The Kaplan-Meier estimation method was used to compare the survival experience of Intrauterine device discontinuation with respect to different covariates. Three parametric accelerated failure time models were compared by using AIC and BIC. Result: Accelerated failure time model with Weibull distribution was found to be appropriate model to fit the data set. The results indicated that the baseline age of the women’s, place of insertion, HIV test, income and educational level of women were significantly associated with time to discontinuation of IUD. Hence, illiterate women with low income and refused to test for HIV had higher hazard rate for time to discontinuation of IUD. Conclusion: From these analyses we conclude that the covariates such as age, place of insertion, Human Immunodeficiency Virus test, income and education are associated with time to discontinuation of Intrauterine device in classical approach. So, we recommended that all stakeholders should be considered when planning and implementing against women’s who utilize Intrauterine device to increase survival time of utilization.